Health consequences of an armed conflict in Zamboanga, Philippines using a syndromic surveillance database - Salazar, Miguel Antonio; Law, Ronald; Winkler, Volker (International journal of environmental research and public health, 2018)
The Zamboanga armed conflict was a 19-day long encounter in the Philippines in 2013 that displaced 119,000 people from their homes. This study describes the health consequences of this complex emergency in different age groups, time periods, and health facilities using data from Surveillance in Post Extreme Emergencies and Disasters (SPEED). This is a descriptive study of the SPEED database spanning 196 days of observation post-disaster and 1065 SPEED reports from 49 health facilities. Evacuation centers and village health centers, both primary care facilities, had the highest number of consults. Common infections and noncommunicable diseases were the most common reasons for consultations, namely, acute respiratory infections, fever, watery diarrhea, skin disease, and hypertension. Infections can be associated with environmental conditions in displaced populations, while hypertension has a high prevalence in the country and implies long-term care. Conflict-related injuries and deaths were not frequently observed due to the volatile situation that influenced health-seeking behavior as well as possible reporting gaps. In conclusion, in complex emergencies, as in natural disasters, wherein early alert and warning for potential outbreaks is crucial, SPEED can assist decision makers on response and recovery interventions. Linkages between SPEED and other surveillance and reporting systems need to be explored.
Gesehen am 20.12.2018